2021
DOI: 10.1155/2021/6615169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rearing Season on Meat and Intramuscular Fat Quality of Beni-Guil Sheep

Abstract: Twenty Beni-Guil-PGI female lambs were used to study the effects of rearing season on meat quality characteristics, fatty acids profile, and lipid content. The animals were reared according to the pastoral-transhumant system in the eastern region of Morocco. The treatments consisted of 10 female lambs reared in summer-autumn (SA) and slaughtered at winter season and 10 female lambs reared in winter-spring (WS) and slaughtered at spring season. After the slaughter, the longissimus lumborum was collected for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The dominant FA in the obtained profile was C18:1 in the meat of two studied groups, followed by C16:0 and C18:0 (Table 1). These results align with those reported by several authors for sheepmeat [4,6]. To fight against certain diseases linked to the current lifestyle, the ratio of PUFA/SFA recommended should be greater than 0.4 and that of n-6/n-3 between 1 and 4.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The dominant FA in the obtained profile was C18:1 in the meat of two studied groups, followed by C16:0 and C18:0 (Table 1). These results align with those reported by several authors for sheepmeat [4,6]. To fight against certain diseases linked to the current lifestyle, the ratio of PUFA/SFA recommended should be greater than 0.4 and that of n-6/n-3 between 1 and 4.…”
Section: Resultssupporting
confidence: 92%
“…Female lambs were slaughtered in their areas of origin in the slaughterhouse. Further details about rearing, diet composition, and slaughter conditions are described by [4]. The sampling was carried out in spring 2018.…”
Section: Animalsmentioning
confidence: 99%
“…However, there is controversy about the influence of multiple factors on this content. In this regard, a recent study demonstrated that rearing season had an important effect on IMF content [ 38 ]. Sheep reared in spring presented higher IMF content than those reared in autumn.…”
Section: Resultsmentioning
confidence: 99%
“…This fact could partially explain the results obtained by us, since the lambs reared in the extensive system (spring of 2019) presented higher values of IMF than those reared in the intensive system (fall of 2018). The differences in the availability and the quality of pasture could be an important factor that could explain the fact that animals reared in spring presented higher IMF than those reared during the autumn, since the two main peaks in lamb feeding change are in winter and spring [ 38 ]. Additionally, the better quality of the pasture also results in a better milk production by the mothers characterized by a high fat content due to a diet rich in fiber, which is undoubtedly related to the higher IMF content in the animals raised in the extensive system (unweaned) than those raised in the intensive production system (weaned).…”
Section: Resultsmentioning
confidence: 99%
“…Female lambs were slaughtered in their areas of origin in a slaughterhouse. Further details about rearing, diet composition and slaughter conditions are described by Belhaj, Mansouri [9]. The study period was from February to July 2018.…”
Section: Animalsmentioning
confidence: 99%